In vivo investigation of fatty goose liver by means of CT - Andrássy-Baka, Gabriella; Romvári, Róbert; Bogenfürst, Ferenc; Molnár, Marcell; Locsmándi, László (Acta Agraria Kaposváriensis, 2002)
Commercial geese (Gray Landes) were examined by means of high resolution spiral computer tomography. Three ganders were scanned six times before (1), within (2–5) and after (6) the force-feeding period. 25–40 serial CT images were taken depending on the liver size. The changes in the volume of the liver and also the characteristic Hounsfield values were determined. The mean values of volume (cm3) were 149, 156, 234, 424, 625, 180 at the 1, 2, 3, 4, 5, 6 measuring times respectively. The characteristic X-ray density values of the liver (75~85, 80, 80, -20, -50 and 55 at the 1, 2, 3, 4, 5, and 6 period respectively) were given in Hounsfield units. The applied in vivo method may be a suitable way to study the quantitative changes of the liver and also to describe the qualitative changes of tissue composition during the force-feeding period.
Keywords: goose liver; computer tomography